ANALYSIS OF FEASIBILITY OF PARK KUMBASARI AS ATTRACTION FRIENDLY TOURISM TO TOURISTS - Purnaya, I Gusti Ketut; Semara, I Made Trisna; Saputra, I Putu David Adi (Journal of Business on Hospitality and Tourism, 2019)
In the present era should be an attraction of tourism can be reached and friendly to all people of both senior tourist and junior tourists. Kumbasari Park is one of the tourist attractions in the city that has been styled and constructed by the Government of Denpasar to become a new tourist attraction. However, the Kumbasari Park has not been fully accessible to all tourists. The purpose of this research is to identify, analyze eligibility and find the perception of travellers to facilities and infrastructure of the Kumbasari Park as a tourist attraction. This research includes exploratory research with data collection techniques i.e. observation, and questionnaires. Data analysis techniques are done in a qualitative and quantitative descriptive. From the results of the study can be concluded that, as a whole Taman kumbasari already worth visiting by all the tourists, there are some categories especially accessibility and amenities that are not yet fully friendly to tourists. The development and reordering of facilities and infrastructure should be done in Kumbasari Park to provide comfort and security to all travelers.